Pengaruh Leadership, Self-Development, Dan Self-Efficacy Terhadap Kinerja Anggota UKM Panorama Photography. (Studi pada UKM Panorama Photography Universitas Islam Malang) - Yuliandri, Diah; Djaelani, Abdul Kodir; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Leadership, Self-Development, and Self-Efficacy on the Performance of UKM Panorama Photography members at Universitas Islam Malang. The research employs a quantitative method with multiple linear regression analysis. Data were collected through questionnaires distributed to 45 UKM members. The results indicate that Leadership, Self-Development, and Self-Efficacy simultaneously have a significant effect on member performance. However, partially, only Self-Development has a positive and significant influence on performance, while Leadership and Self-Efficacy do not significantly affect it. The implications of this research provide insights for organizational management to prioritize member self-development to enhance performance. Keywords: Leadership, Self-Development, Self-Efficacy, Performance, UKM Panorama Photography